Antioxidant and Antiulcer Potential on leaves of Brassica nigra L. against Gastric Ulcer - Atul Tripathi; Rakesh Punekar; Vishal Jain; Chandra Kishore Tyagi; Amol Chandekar; Amber Vyas (International Journal of Phytomedicine, 2017)
In the present study, anti-ulcerative effects of extract of Brassica nigra L. leaves were investigated in pylorus ligation and aspirin-induced gastric ulcer models in rats. In present study antiulcer effect of ethanolic extract of Brassica nigra leaves is well understood by total acidity, free acidity, and ulcer index of different groups of animals in both the model viz. Pylorus ligation model & Aspirin induced gastric ulcer in experimental rats when compared the test group with control and standard group. The percentage of ulcer inhibition was observed in pylorus ligated model was as follows: standard, BNLE 100mg/kg, BNLE 200mg/kg and BNLE 300mg/kg 55.76%, 30.96%, 49.54% and 51.35% respectively. The mechanism of gastric ulcer healing is not well understood and further study is needed to evaluate the specific phytoconstituents responsible for the gastric ulcer healing but on the basis of present study it can be concluded that this gastric healing potential may be due to the pharmacological effect played by the different phytoconstituents present in the ethanolic extract of Brassica nigra leaves for prevention of gastric mucosa or by the antioxidant potential of the leaves which is evaluated during the DPPH free radical scavenging activity.